TEACHER PERFORMANCE, ORGANIZATIONAL CULTURE, COMPENSATION, AND SPIRITUAL LEADERSHIP: A LITERATURE STUDY - Syahid Syahid; Fauzul Iman; Supardi Supardi (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2022)
This study aims to explore and analyze theories of organizational culture, compensation, and spiritual leadership and how they affect performance based on preliminary studies. The method used in this study is literature study. Relevant data is searched through books and scientific journals of international and national repute published on Google Scholar. The steps of data analysis consist of editing, organizing, and making conclusions. The results of the study reveal that there is a significant impact of organizational culture, compensation, and spiritual leadership on performance. However, research on madrasas as religious educational institutions has not yet been carried out. The study recommendations suggest that further research be carried out regarding the variables studied.